PENGEMBANGAN MEDIA PEMBELAJARAN AKIDAH DENGAN KONSEP “QURANI” BERBASIS ICT UNTUK SISWA SEKOLAH - Usup Romli; Jenuri .; Dina Mayadiana Suwarma; Mohammad Rindu Fajar Islamy; Muhamad Parhan (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
DEVELOPMENT OF LEARNING MEDIA FAITH OF ICT BASED WITH THE CONCEPT OF “QURANI” ICT FOR PRIMARY SCHOOL STUDENTSThis study aims to produce learning media for Akidah Akhlak class I SD in the form of ICT-based learning using the Microsoft Powerpoint Interactive application. Media development is the conversation of educational experts today, with the development of technology, it is hoped that the learning process can improve students' understanding of learning material. The inculcation of faith values based on the Al-Quran becomes a bridge for the realization of students with good achievements and good morals. This product combines Borg's research concept and the QURANI method developed by education expert Muhamad Sa'id Mursi. The content of research products refers to the 2014 curriculum for grade I elementary school students related to akidah akhlak material. The method used is based on qualitative research through the developed interactive powerpoint media product validation technique. This research was validated by 3 expert teams, where 2 people involved lecturers of Islamic Education at the University of Pendidikan Indonesia, and 1 person was from the Curriculum Expert Team.